What Drives Residential Land Expansion and Densification? An Analysis of Growing and Shrinking Regions - Eda Ustaoglu; Chris Jacobs-Crisioni (Land, 2022)
While the driving factors of urban growth and urban sprawl have repeatedly been studied, the implications for residential densities presumably differ in growing and shrinking regions. Thus far, those differences have received little attention. This paper examined the dynamics of urban growth and shrinkage across EU regions, using residential densities as an explanatory factor to analyse the underlying dynamics. To do so, detailed spatial data on various potentially relevant factors were used in regression methods to establish the relevance of those factors for residential expansion and densification in growing and shrinking EU regions between the years 2000 and 2010. We found that expansion and densification processes are affected by population size, prior residential density, land supply, accessibility, agricultural land rent, physical factors, public regulation, and regional characteristics. The results of this study can confirm that residential expansion is driven differently in declining regions than in regions with population growth. Models explaining residential density changes also yield different results in declining regions.